The Impact of Corporate Governance on the Quality of Financial Reports Moderated by Profitability (Case Study of Indonesia and Türkiye) - Dedi Kurniawan; Ali Alagöz; Saeed Hassan Mohamed (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: This study investigates the impact of board independence, board competence, board diversity, and profitability on financial reporting quality (FRQ) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the Istanbul Stock Exchange (BIST). By comparing two developing countries with different institutional environments, this study seeks to identify contextual elements that determine the efficiency of corporate governance. Method: This research employs a quantitative method, making use of secondary data from listed industrial companies' annual reports for fiscal years 2023 and 2024 (128 firm-year observations). Panel data regression analysis with a random effects model (REM) is used to evaluate FRQ, measured as discretionary accruals derived from the Jones model. The Seemingly Unrelated Estimation Test (SUEST) is used as a post-estimation tool to statistically compare regression coefficients across country samples. Findings: In the Indonesian sample, board independence and board expertise do not significantly affect FRQ, while board diversity and profitability do. Profitability positively moderates each governance variable's correlation with FRQ in the Indonesian sample. In the Turkish sample, no governance or profitability variables yield significant results. The SUEST coefficient comparison test indicates that the differences in the effects of governance variables between the two countries are not statistically significant at conventional levels. Implications: The findings indicate that the national institutional framework has a significant impact on how successful corporate governance mechanisms are. Market-based incentives appear to be more dominant in Indonesia, while regulatory compliance drives reporting quality in Turkey. These findings have significant ramifications for governance professionals and regulators in developing nations. Novelty/Value: This study adds cross-national evidence to the field on comparative governance from two institutionally distinct emerging markets. It also integrates institutional theory and signalling theory to explain how national context shapes governance effectiveness. The SUEST post-estimation procedure is applied to formally test whether cross-country coefficient differences are statistically significant.